1993
DOI: 10.1021/j100109a013
|View full text |Cite
|
Sign up to set email alerts
|

Matrix isolation of acetonitrile clusters from a pulsed supersonic beam

Abstract: Acetonitrile clusters (CH$N),, different from the antiparallel dimer have so far not been observed in cryogenic matrices. The combination of molecular beam and matrix isolation technique enabled us to evidence the presence of larger clusters in Ar matrix. In these experiments the task of the molecular beam is the production of the clusters via an adiabatic expansion under properly selected conditions. On the other hand, the matrix is needed for the conservation of the clusters. essentially diagnostic relevance. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…The appearance of larger acetonitrile clusters should become more likely for significantly higher deposition rates. So far such large spe- cies have, however, only been observed after adiabatic instead of thermal effusive expansion prior to deposition [5].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The appearance of larger acetonitrile clusters should become more likely for significantly higher deposition rates. So far such large spe- cies have, however, only been observed after adiabatic instead of thermal effusive expansion prior to deposition [5].…”
Section: Resultsmentioning
confidence: 97%
“…In fact, this barrier is likely to be smaller for HTM because its unit cell structure (Fig. 2b) is based on pairs of antiparallel oriented acetonitrile molecules as elementary constituents [3,5]. In order to build up the LTM from antiparallel dimers a considerable amount of energy has to be invested for the reorientation of acetonitrile monomers out of the energetically favoured geometry in the stable dimer (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…This is comparable to the methanol dimer bond energy, which is reported within a range of 3.45 eV [45] to 6.04 eV [37], suggesting that the density of acetonitrile dimer may be comparable to that for methanol dimer. Significant dimer:monomer ratios have been measured in supersonic expansions [46]; however, this is not representative of the high-temperature environment of an APPI source.…”
Section: Generation Of Solvent Ions From Acetonitrile With Appimentioning
confidence: 97%
“…42 Acetonitrile clusters have already been the subject of both experimental and theoretical studies. [43][44][45][46][47][48][49][50][51][52][53] Because of the large dipole moment of acetonitrile ͑3.9 D͒, the interactions within these clusters are dominated essentially by dipole-dipole forces, and the lowest energy structures reflect the favorable antiparallel pairing of the molecular dipoles. Molecular dynamics ͑MD͒ and Monte Carlo ͑MC͒ studies have shown that the antiparallel pairing of the dipoles may lead to rigid solidlike structures of the n-even clusters with melting transition temperatures considerably higher than those of the n-odd clusters.…”
Section: Introductionmentioning
confidence: 99%